Numerical Investigation in Augmentation of Heat Transfer in a Rectangular Duct Using Al2O3 and CuO Nanofluids - Christopher, David Santosh; Atiso, Tsegaye Alemayehu; Markos, Mebratu (Asian Review of Mechanical Engineering, 2020)
A numerical investigation was conducted to predict the greater thermal enhancement in the rectangular duct using different nanofluids – Aluminum oxide (Al2 O3) and Copper oxide (CuO) are employed in the investigation and magnitude are compared with base fluid to ascertain the augmentation of thermal efficiency. Ansys-Fluent 13 used for simulation to identify the augmentation of heat transfer among fluids. A simulation conducted in Laminar flow with Reynolds number (Re) ranges from 20 to 40 at constant heat flux 2000 W/m2. The research reported the contour of temperature distribution, pressure variation, and magnitude velocity, Result reveals that copper oxide nanofluids have produced significant thermal performances than other nanofluid particles.